Perlindungan Data Pribadi Dalam Perspektif Sadd Dzari’ah - Mohammad Farid Fad (MUAMALATUNA, 2021)
Abstract In the world of computing and digital, an individual is required to recognize and define the boundaries or boundaries of his preferences in order to reach agreement on the status of his privacy in a particular context or space. In other words, each individual should acquire the right to use his/her own personal data, which will ensure a more active role in the management of his/her personal data. While on the other hand, personal data or information has become something that is very valuable, as well as vulnerable as a commodity so that it poses a risk of vulnerability to misuse or theft of personal data. For this reason, it is necessary to analyze risk mitigation in a syar'i manner in order to avoid the crime of theft and misuse of personal data in cyberspace called the sadd dzari'ah method. This research uses a qualitative approach. Data collection methods used in this study are literature, documentation and observation methods. In analyzing the data that has been collected, the researcher will use descriptive-analytical analysis with ushuliyah approach. The findings of this study are in the perspective of sadd dzari'ah, personal data contains honor and personal dignity that should not be disturbed. When there is misuse of data, it creates a danger (mudharat) in the form of damage to a person's dignity (hifz al-irdh) even though Islamic law as much as possible creates benefits for humans. Therefore, the Government is obliged to draw up a Personal Data Protection Law in order to create a protected and guaranteed digital ecosystem. Keywords: Protection, Personal Data, Sadd Dzari’ah. Abstrak Dalam dunia komputasi dan digital, seorang individu dituntut untuk mengenali dan menetapkan garis batas atau batasan preferensinya untuk mencapai kesepakatan tentang status privasinya dalam konteks atau ruang tertentu. Dengan kata lain, masing-masing individu harus memperoleh hak untuk menggunakan data pribadinya sendiri, yang akan memastikan peran yang lebih aktif dalam pengelolaan data pribadinya. Sementara di sisi yang lain, data atau informasi pribadi telah menjadi sesuatu yang sangat berharga, sekaligus rentan sebagai komoditas hingga menimbulkan resiko kerawanan penyalahgunaan ataupun pencurian data pribadi. Untuk itu diperlukan analitis mitigasi resiko secara syar’i demi terhindar dari kejahatan pencurian dan penyalahgunaan data pribadi di ruang siber yang disebut metode sadd dzari’ah. Penelitian ini memakai pendekatan kualitatif. Metode pengumpulan data yang dipakai dalam penelitian ini adalah metode literature, dokumentasi dan observasi. Dalam menganalisis data yang telah terkumpul, peneliti akan menggunakan analisis deskriptif-analitis dengan pendekatan ushuliyah. Temuan penelitian ini adalah dalam perspektif sadd dzari’ah, data pribadi memuat kehormatan, dan martabat pribadi yang tidak boleh diganggu. Ketika terjadi penyalahgunaan data, maka menimbulkan bahaya (mudharat) berupa rusaknya harkat dan martabat seseorang (hifz al-irdh) padahal syariat Islam sebisa mungkin mewujudkan kemaslahatan bagi manusia. Oleh karena itu, Pemerintah wajib menyusun Undang-Undang Perlindungan Data Pribadi demi menciptakan ekosistem digital yang terlindungi dan terjamin keamanannya. Kata Kunci: Perlindungan, Data Pribadi, Sadd Dzari’ah.